2016
DOI: 10.1111/1750-3841.13253
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Glycosidase from Non‐Saccharomyces Isolates for Enhancement of Wine Aroma

Abstract: The aim of this work was to rapidly screen indigenous yeasts with high levels of β-glucosidase activity and assess the potential of glycosidase extracts for aroma enhancement in winemaking. A semiquantitative colorimetric assay was applied using 96-well plates to screen yeasts from 3 different regions of China. Isolates with high β-glucosidase activity were confirmed by the commonly used pNP assay. Among 493 non-Saccharomyces isolates belonging to 8 generas, 3 isolates were selected for their high levels of β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Thus, wines treated with H . uvarum β ‐glucosidase showed higher sensory scores for 'tropical fruit', 'berry', 'floral' and 'nut aroma' and lower scores for 'green' than control wines treated with a commercial preparation of β ‐glucosidase (Hu et al ., ). Mixed cultures of H .…”
Section: Hanseniaspora Sppmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, wines treated with H . uvarum β ‐glucosidase showed higher sensory scores for 'tropical fruit', 'berry', 'floral' and 'nut aroma' and lower scores for 'green' than control wines treated with a commercial preparation of β ‐glucosidase (Hu et al ., ). Mixed cultures of H .…”
Section: Hanseniaspora Sppmentioning
confidence: 97%
“…uvarum and H . vineae strains have shown interesting enzyme activities such as β ‐glucosidase and β ‐xylosidase that could increase the release of some volatile compounds during winemaking (Hu et al ., ; Lopez et al ., ). Indeed, pilot‐scale (200 kg) Pinot Noir must treated with β ‐glucosidase from H .…”
Section: Hanseniaspora Sppmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of non-Saccharomyces in fermentative processes results in greater production of volatile compounds of interest (Oliveira et al 2005). Indeed, controlled mixed inoculations with S. cerevisiae and non-Saccharomyces have been shown as a possibility to increase the aroma complexity and sensorial characteristics of fermented beverages due to higher production of secondary metabolites (Hu et al 2016;Whitener et al 2017). Previous studies using mixed inoculum of Meyerozyma caribbica and S. cerevisiae to produce sugarcane spirit reported that the variety and quantity of desirable volatile compounds were considerably higher than those found for pure S. cerevisiae (Duarte et al 2013;Amorim et al 2016).…”
Section: Introductionmentioning
confidence: 99%